Mechanically robust waveguide‐integration and beam shaping of terahertz quantum cascade lasers. Issue 12 (1st June 2015) - Valavanis, A.; Han, Y.J.; Brewster, N.; Dean, P.; Dong, R.; Bushnell, L.; Oldfield, M.; Zhu, J.X.; Li, L.H.; Davies, A.G.; Ellison, B.; Linfield, E.H.
Abstract : Terahertz‐frequency quantum cascade lasers (THz QCLs) have numerous potential applications as 1–5 THz radiation sources in space science, biomedical and industrial sensing scenarios. However, the key obstacles to their wide‐scale adoption outside laboratory environments have included their poor far‐field beam quality and the lack of mechanically robust schemes that allow integration of QCLs with THz waveguides, mixers and other system components. A block integration scheme is presented, in which a continuous‐wave ∼3.4 THz double‐metal QCL is bonded into a precision‐machined rectangular waveguide within a copper heat‐sink block. This highly reproducible approach provides a single‐lobed far‐field beam profile with a divergence of ≲20°, and with no significant degradation in threshold current or in the range of operating temperatures.